KCC3a, a Strong Candidate Pathway for K+ Loss in Alkalemia - Ferdaus, Mohammed Zubaerul; Terker, Andrew Scott; Koumangoye, Rainelli; Delpire, Eric (Frontiers in Cell and Developmental Biology, 2022)
Loss-of-function mutations in the human potassium chloride cotransporter-3 (KCC3) cause a hereditary motor sensory neuropathy associated with agenesis of the corpus callosum. While recapitulating the neuropathy, KCC3 knockout mice also exhibit high blood pressure. This phenotype is believed to have neurogenic and/or vascular origins. The role of KCC3 in the kidney is poorly understood. KCC3 is encoded by two major isoforms originating from alternative promoters: KCC3a and KCC3b, with KCC3b being the predominant transcript in kidney. Although the transporter has previously been localized to the proximal tubule, we show here unique expression of the KCC3a isoform in the connecting tubule. Using a KCC3a-specific polyclonal antibody validated for both immunofluorescence and immunoblotting, we showed intense KCC3a signal restricted to cortical intercalated cells. No overlap is detected between KCC3a and sodium chloride cotransporter (NCC), a distal convoluted tubule (DCT) marker; or between KCC3a and ENaC or calbindin, which are both principal cell markers. KCC3a signal was observed in cells expressing the apical V-ATPase and pendrin, establishing a unique expression pattern characteristic of intercalated cells of type B or type non-A/non-B. We further show that treatment of wild-type mice with hydrochlorothiazide, amiloride, or fed a K+ deficient diet up-regulates KCC3a levels, suggesting that volume depletion increases KCC3a abundance. This hypothesis was confirmed by showing higher abundance of KCC3a protein after 23-hrs water restriction or after placing the mice on a low salt diet. More importantly, abundance of the Cl-/HCO3- exchanger, pendrin, which is known to secrete bicarbonate in alkalotic conditions, was significantly diminished in KCC3 knockout mice. In addition, KCC3a abundance increased significantly alongside pendrin abundance in bicarbonate-treated alkalotic mice, providing a credible mechanism for K+ loss in metabolic alkalosis.